Tackling the blind spot of poor-quality medicines in Universal Health Coverage - E. S. F. Orubu; C. Ching; M. H. Zaman; V. J. Wirtz (Taylor & Francis Group, 2020)
Background Universal Health Coverage (UHC) is challenged by the prevalence of poor-quality medicines, those that either do not meet required specifications (substandard) or are outrightly fraudulent (falsified), especially in Low- and Middle-Income Countries, LMICs. Whereas poor-quality medicines are a significant burden in these countries, medicine quality still remains a neglected component of UHC programs. This article describes key barriers to quality medicines and presents five select approaches leveraging the scale-up of UHC for medicine quality assurance. Main body Barriers to medicine quality assurance, while numerous, are described in five key inter-related domains as: low political priority, weak regulatory systems capacity, poor access to accredited facilities and licensed outlets, medicine manufacturing and other supply-chain challenges, and lack of public awareness. Five select approaches for leveraging the scale-up of UHC for medicine quality assurance in LMICs are (1): political commitment (2) strengthening the capacity of regulatory authorities and investment in detection technologies as part of national security (3); licensing of medicines outlets and expanding pharmacovigilance (4); strengthening the supply-chain; and (5) public awareness and participation. Conclusions Unchecked, poor-quality medicines can jeopardize UHC. National governments in LMICs need to prioritize medicine quality assurance through enforcing policies, regulatory strengthening and investments in technologies. Healthcare facilities and insurance schemes under UHC also play critical roles through incorporating medicine quality assurance into procurement practices and by promoting awareness among beneficiaries. Tackling medicine quality with a committed systems approach will enhance progress towards UHC implementation.